Impact of New 5 Year Automobile Policy (2016-21) on the Profitability of Major Players in the Automobile Industry of Pakistan - Mustafa, Sadaf; Begum, Rukhshinda; Nisar, Syeda Kanza; Osama, Ahmed (European Scientific Journal, ESJ, 2018)
This research paper discusses the influence of new five year automobile policy announced by Economic Coordination Committee (ECC) in March 2016 for the period from 2016 to 2021 comparing with the old auto policy announced by the Government of Pakistan. The crucial point of this paper is to find the critical aspects of new auto policy and their impact on the profitability of major players in automobile industry of Pakistan. Main objectives of this policy are to help increase the volume with improved quality, catch the attention of investors, creating an extensive competitive environment, minimizing costs, technological improvement, satisfy all stakeholders through a Balance between tariffs and growth, customer satisfaction and Eliminating Monopoly of Existing Car Manufacturers. The important rationale of this paper is to have a look on the prevailing situation of automobile industry and the potential of this industry after the implementation of new auto-policy for 2016-21. It is to analyse whether this policy may influence profitability of the firms those have created their monopoly in this sector of Pakistan. The results of the study reveal that the profitability of major players of the automobile industry those were creating monopolies is not expected to decline even after the new policy. It may because of the trust of people on the local makes or expected ease in maintenance than those of the imported ones. However, the circumstances may change based on the customers’ behavior that may cause the shift of their profit share to the New Entrants. Nevertheless, exploring the industrial alliance in this sector globally is of high importance for better quality, reasonable costs, fuel efficiency and striking designs. Various studies have been conducted to highlight the impacts of different policies announced by the governments for automobile industry worldwide and for the Pakistan as well. Consequently, this study will be useful to seek out the probable challenges to confront in the automobile industry and to provide support for the future policies related to automobile companies and interrelated businesses like leasing, insurance, tracking and auto finance.